2011
DOI: 10.1159/000332348
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of an Upper Airway Dilator Muscle in Aged Obese Male Rats

Abstract: Background: Age, obesity and male sex are risk factors for the development of obstructive sleep apnoea syndrome. Objective: We examined structural and functional properties of the sternohyoid muscle in young lean and aged obese male rats. We hypothesized that the aged muscle would be vulnerable to oxidative stress (hypoxia). Methods: Isometric contractile and endurance properties of the sternohyoid muscle were assessed in vitro with or without the superoxide scavenger Tempol (10 mM). Muscle fibre size and dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…We also observed an increase in diaphragm force with maturation, which is consistent with several previous studies in the same species at similar ages (Sieck et al 1991 b , 1996; Watchko et al 1992; Johnson et al 1994; Fratacci et al 1996 a ; Zhan et al 1998; Geiger et al 2001). Of note, we observed that respiratory muscle peak specific force in early postnatal development is considerably lower than that reported for adult muscles (Zhan et al 1998; Skelly et al 2010, 2011), consistent with previous observations (Zhan et al 1998). It has been suggested that changes in skeletal muscle contractile properties during development are associated with alterations in the contractile protein composition of muscle fibres.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed an increase in diaphragm force with maturation, which is consistent with several previous studies in the same species at similar ages (Sieck et al 1991 b , 1996; Watchko et al 1992; Johnson et al 1994; Fratacci et al 1996 a ; Zhan et al 1998; Geiger et al 2001). Of note, we observed that respiratory muscle peak specific force in early postnatal development is considerably lower than that reported for adult muscles (Zhan et al 1998; Skelly et al 2010, 2011), consistent with previous observations (Zhan et al 1998). It has been suggested that changes in skeletal muscle contractile properties during development are associated with alterations in the contractile protein composition of muscle fibres.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, in this study, we sought to characterize the postnatal developmental changes in sternohyoid and diaphragm muscle contractile and endurance properties, MHC isoform expression and oxidative and glycolytic enzyme activities. We hypothesized that the maturational programme would differ in the two muscles during postnatal development despite their complementary functions given the dramatic differences reported for the two muscles in adult mammals (Metzger et al 1985; Johnson et al 1994; van Lunteren & Brass, 1996; O’Halloran et al 2002; El‐Khoury et al 2003; Polla et al 2004; McMorrow et al 2011; Skelly et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we do not expect that aging inhibited the training responses of ITTO-20 animals, supported by the lack of significant differences between the ITTO and ITTO-20 groups [59]. While rat body mass and fiber size increase through late adulthood [60], [61], we did not find larger fibers in the older ITTO-20 than ITTO animals. Alternatively, the 20-minute daily regime resulted in more handling of the animals, which one could speculate served as a stressor.…”
Section: Discussionmentioning
confidence: 54%
“…However, LTF-driven increases in ventilatory output are mediated in part by slight increases in oxidative stress and other signaling pathways (106 -108) and have been successfully harnessed as an approach aiming to rehabilitate patients after spinal cord injury (69,128,129). However, LTF-generating paradigms could lead to long-term muscle fatigue with remodeling of the upper airway muscles and diaphragm and ultimately deleterious effects on motor control (53, [175][176][177][178]. This dysfunction emerges as highly dependent on factors such as age (177) or sex (176).…”
Section: Whenmentioning
confidence: 99%
“…However, LTF-generating paradigms could lead to long-term muscle fatigue with remodeling of the upper airway muscles and diaphragm and ultimately deleterious effects on motor control (53, [175][176][177][178]. This dysfunction emerges as highly dependent on factors such as age (177) or sex (176).…”
Section: Whenmentioning
confidence: 99%